Reliability of torque expression by the Invisalign® appliance: A retrospective study - Gaddam Raj; Freer Elissa; Kerr Brett; Weir Tony (Sciendo, 2021)
Introduction: Incisal torque in orthodontics has always been important due to its relationship with smile aesthetics and the stability of a final treatment outcome. The aim of this study was to quantify the accuracy of torque expression predicted by ClinCheck® planning associated with Invisalign® treatment, compared to clinical outcomes.